Microvascular Reconstruction of Segmental Mandibular Defects without Tracheostomy. (February 2015) - Moubayed, Sami P.; Barker, Daniel A.; Razfar, Ali; Nabili, Vishad; Blackwell, Keith E.
Objective: To report our experience with mandibular resection and reconstruction using vascularized bone-containing free flaps without an elective tracheostomy. Study Design: Case series with chart review. Setting: Tertiary referral hospital center. Subjects and Methods: Sixty-six patients undergoing mandibular reconstruction with vascularized bone-containing free flaps without an elective tracheostomy were identified between 1995 and 2013. We describe patient, tumor, and surgical factors and report perioperative outcomes in this population. Results: Most patients underwent fibula free flap reconstruction (n = 61, 92.44%). The 4 most frequent indications for resection were osteoradionecrosis, parotid carcinoma, oral squamous cell carcinoma, and osteomyelitis. Bone defects ranging from 4.0 to 13.0 cm were reconstructed, and associated soft-tissue defects were reconstructed with skin paddle sizes ranging from 24.0 to 450.0 cm 2 . There was only 1 patient with a bilateral central mandibular defect, and there were no tongue/pharyngeal soft-tissue defects or bilateral neck dissections. One case required emergent tracheostomy on postoperative day 1, and 2 more patients developed respiratory complications. There were no cases of perioperative death or flap failure. Conclusion: Mandibular free flap reconstruction is feasible without an elective tracheostomy in a subset of carefully selected patients without bilateral central mandibular defects, tongue/pharynx defects, or bilateral neck dissection.